INFLUENCE OF QUARTZITE WASTE FROM INDUCTION FURNACES ON THE HYDRATION AND HARDENING PROCESSES OF PORTLAND CEMENT (European Journal of Interdisciplinary Research and Development, 2026)
This study investigates the influence of quartzite waste from induction furnaces on the hydration, hardening, and phase formation processes of Portland cement. Composite cements were produced by partial replacement of clinker with quartzite waste in an amount of 15–20 wt.%. X-ray diffraction analysis was used to examine changes in the mineralogical composition and microstructure of cement stone at curing ages of 3, 7, 14, and 28 days. It was established that the incorporation of quartzite waste intensifies pozzolanic reactions, reduces the content of portlandite, and promotes the formation of a well-developed amorphous C–S–H gel phase, which leads to densification of the cement stone structure and enhancement of its strength characteristics.